2008
DOI: 10.1002/elps.200700549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stern layer conductance on electrokinetic energy conversion in nanofluidic channels

Abstract: A thermo-electro-hydro-dynamic model is developed to analytically account for the effects of Stern layer conductance on electrokinetic energy conversion in nanofluidic channels. The optimum electrokinetic devices performance is dependent on a figure of merit, in which the Stern layer conductance appears as a nondimensional Dukhin number. Such surface conductance is found to significantly reduce the figure of merit and thus the efficiency and power output. This finding may explain why the recently measured elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 32 publications
0
56
2
Order By: Relevance
“…Here, f is the Stokes-Einstein friction factor, f = k B T D and D is the diffusion coefficient, σ s is the conductivity of the Stern layer (Masliyah and Bhattacharjee 2006;Lee et al 2012;Davidson and Xuan 2008). It is important to note that since we use a linear viscoelastic model, the f factor presented here is not dependent on the power law exponent [denoted as β in ] which is solely used for a power law (inelastic) fluid.…”
Section: Ionic Currentmentioning
confidence: 99%
“…Here, f is the Stokes-Einstein friction factor, f = k B T D and D is the diffusion coefficient, σ s is the conductivity of the Stern layer (Masliyah and Bhattacharjee 2006;Lee et al 2012;Davidson and Xuan 2008). It is important to note that since we use a linear viscoelastic model, the f factor presented here is not dependent on the power law exponent [denoted as β in ] which is solely used for a power law (inelastic) fluid.…”
Section: Ionic Currentmentioning
confidence: 99%
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…7,16,17 Electrokinetic current generation, like all electrokinetic effects, relies on an anisotropic ion distribution at an interface. Ions at the solid surface engender surface conduction and provide an additional route for dissipating charge, reducing conversion efficiency.…”
mentioning
confidence: 99%